General and Abdominal Adiposity and Risk of Death in HBV Versus Non-HBV Carriers: A 10-Year Population-based Cohort Study. Issue 2 (January 2016) - Lin, Wen-Yuan; Peng, Cheng-Yuan; Lin, Cheng-Chieh; Davidson, Lance E.; Pi-Sunyer, F. Xavier; Sung, Pei-Kun; Huang, Kuo-Chin
Abstract : Abstract: Both obesity and hepatitis B virus (HBV) infection increase the risk of death. We investigate the association between general and central obesity and all-cause mortality among adult Taiwanese HBV versus non-HBV carriers. A total of 19, 850 HBV carriers and non-hepatitis C virus (HCV) carriers, aged 20 years and older at enrollment in 1998 to 1999 in Taiwan, were matched to 79, 400 non-HBV and non-HCV carriers (1:4). Cox proportional-hazards models were used to estimate the relative risks for all-cause mortality during a maximum follow-up period of 10 years. Four obesity-related anthropometric indices—body mass index (BMI), waist circumference, waist-to-hip ratio, and waist-to-height ratio—were the main variables of interest. During the follow-up period, 628 and 2366 participants died among HBV and non-HBV carriers, respectively. Both underweight and general obesity were associated with an increased risk of death. The highest risk of all-cause death in relation to BMI was found in the HBV carriers with underweight (BMI <18.5 kg/m 2 ) and non-HBV carriers with obesity (BMI ≥30 kg/m 2 ). The lowest risks of all-cause death in relation to abdominal adiposity were found at the third quartiles of waist circumference, waist-to-hip ratio, and waist-to-height ratio among HBV carriers, but in the second quartiles among non-HBV carriers. For those with pre-existing liver disease among HBV carriers, patients with underweight have higher risk of death than those with obesity. Hepatitis B virus carriers with underweight have higher risk of death than non-HBV carriers. HBV carriers with mild abdominal obesity have the lowest risk of death, but not in the non-HBV carriers.